Evaluasi Kemampuan Lahan sebagai Kawasan Pariwisata di Pantai Sepanjang, Dusun Nglaos, Desa Kemadang, Kecamatan Tanjungsari, Kabupaten Gunungkidul, Provinsi Daerah Istimewa Yogyakarta - Andi Sungkowo; Farida Afriani Astuti; Farid Zulfa Fakhruddin (Jurusan Teknik Lingkungan, FTM, Universitas Pembangunan Nasional “Veteran” Yogyakarta, 2020)
Sepanjang Beach is a tourist area located in Nglaos Hamlet, Kemadang Village, Tanjungsari District, Gunungkidul Regency. As a tourist area, this beach has a limiting factor that reduces the aspect of tourism in the form of a tidal wave that can endanger tourists. The tidal events that occurred on the coast The last one occurred on July 24, 2018 which caused 25 units of the gazebo to disappear and 115 units of the gazebo to suffer severe damage. So research is carried out with the aim of evaluating the ability of Sepanjang beach as a tourism area. Evaluation is done by scoring method. The parameters of land capability measured are soil texture, surface slope, drainage, depth of ground water, and erosion. The results of the calculation of land capability based on aspects of land capability obtained 2 classes of land capability, namely medium and good. Judging from the results of the land capability, the research location is considered to have a good level of land capability as a tourism area. Keywords: Evaluation, Land Capability, Tourism